Effect of silicon on sensitivity of SPR biosensor using hybrid nanostructure of black phosphorus and MXene - Kumar, Rajeev; Pal, Sarika; Verma, Alka; Prajapati, Y.K.; Saini, J.P. (Superlattices and microstructures, 2020)
In this work, we explored the sensitivity of surface plasmon resonance biosensor on using silicon and hybrid nanostructure of black phosphorus and MXene (Ti3C2Tx) at 633 nm. To investigate the prominence of each layer, we categorized it into Kretschmann configuration based different simple structures. The performance of each sensor structure is theoretically analyzed after systematically optimizing their layer thicknesses and layer numbers. Highest sensitivity (264 0/RIU) and optimum figure of merit (41.25/RIU) is achieved for the proposed SPR structure. Results shows, pronounced sensitivity enhancement of 127.58% for proposed sensor over conventional SPR. Enhanced sensitivity is attained due to attractive optical sensing properties of silicon (high refractive index), black phosphorus (high charge carrier mobility, carrier confinement) and MXene-Ti3C2Tx (high metallic conductivity, biocompatibility, larger hydrophilic surface area). The proposed design can be fabricated as SPR chip by careful control of Ti3C2Tx surface terminations with available fabrication technologies. •Proposed SPR biosensor is based on silicon and hybrid nanostructure of black phosphorus and MXene-Ti3C2TX.•Attained highest sensitivity (264ο/RIU) among all MXene-Ti3C2TX based SPR biosensor proposed till date.•Sensitivity enhancement of 127.58% over conventional SPR sensor.•BP layers plays important role in sensitivity improvement.•Larger surface area and hydrophilic surfaces of MXene-Ti3C2TX makes it efficient for SPR biosensing application.